Treatment of Displaced Intra-articular Calcaneal Fractures With an Interlocking Nail (C-Nail). Issue 11 (November 2020) - Veliceasa, Bogdan; Filip, Alexandru; Pinzaru, Roxana; Pertea, Mihaela; Ciuntu, Bogdan; Alexa, Ovidiu
Abstract : Objectives: To assess the outcome of the sinus tarsi approach and C-Nail fixation of displaced intra-articular calcaneal fractures (DIACFs). Design: Prospective study. Setting: University Trauma Department. Patients: Sixty-four patients (mean age 44.3 years, 48 men and 16 women) with 75 DIACFs were treated between October 1, 2016 and December 31, 2018. Intervention: In all cases, the posterior facet was reduced through the sinus tarsi approach and fixed with one or 2 screws. After reducing all fragments to the articular block, the final fixation was performed percutaneously with C-Nail, locked with 6 screws. Main Outcome Measurements: Patients were assessed for restoration of the Böhler angle, complications, and overall fracture reduction. To assess the functional outcome, we used the Mean American Orthopaedic Foot & Ankle Society Ankle-Hindfoot Score and Maryland Foot Score after 12 months. Results: The Böhler angle improved from −0.5 degrees preoperatively to 28.6 degrees postoperatively. The articular step-off was reduced from 5.4 mm preoperatively to 0.6 mm postoperatively. The postoperative radiologic calcaneal score was 2.9, on average. Superficial wound edge necrosis was seen in 3 patients (4%) and superficial infection was observed in one (1.3%). After a 1-year follow-up, we recorded a mean American Orthopaedic Foot & Ankle Society Ankle-Hindfoot Score of 90.2 and a mean Maryland Foot Score of 91.2. Conclusions: After obtaining an anatomic reduction of the articular surface of the posterior facet with lag screws, the C-Nail represented a viable alternative to plate stabilization in the treatment of DIACFs, combining primary stability with low soft tissue complications. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.